Green Innovation, Carbon Emission Disclosure, and Managerial Ownership: A Panel Data Analysis of Firm Value in Indonesia’s Basic Materials Sector - Purnomo, Listiya Ike; Santoso, Adela Devanti (Jurnal Akuntansi, 2025)
Abstract Purpose – This research seeks to investigate the influence of green innovation, carbon emissions disclosure, and managerial ownership on the value of companies within the basic materials sector that are listed on the Indonesia Stock Exchange from 2019 to 2023. Design/Methodology/Approach – This research employs purposive sampling, focusing on primary material companies that are listed in Indonesia as the key criterion. The final sample comprised 7 companies, with a duration of observation spanning 5 years, resulting in a total of 35 data points. This research employs a random effects model of panel data regression analysis to examine the relationship among the research variables. Findings – The study results obtained from the random effects model indicate that green innovation and managerial ownership do not have a significant impact on the firm's value. On the other hand, revealing carbon emissions positively and significantly influences the firm's value. These findings emphasize the importance of environmental accountability, particularly through transparent reporting of carbon emissions, as a vital approach to increase company value and foster investor confidence. Research limitations/Implications – This study is limited to one industry sector only, so the results cannot be generalized to other industry sectors outside the sector. The use of purposive sampling tends to produce a homogeneous sample, which may cause selection bias and affect the external validity of the study. Keywords: Carbon Emission Disclosure, Firm Value, Green Innovation, Managerial Ownership